2022
DOI: 10.1186/s13011-022-00444-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in addiction and recovery gains according to gender – gender barriers and specific differences in overall strengths growth

Abstract: Background There is growing evidence on the importance of a gendered understanding of recovery. Gender differences have been reported in relation to the nature and extent of substance use, pathways to and through substance use disorder and recovery capital acquisition and maintenance. There is little existing research on factors associated with recovery capital growth by gender. Methods The current paper uses the European Life in Recovery database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Previous correlates of higher RC have been lower‐risk substance use (as compared to higher‐risk substance use), 15 stable housing, 18 and employment 18 . Predictors of RC growth have also differed by sex, with work from our group showing that males exhibit differential growth driven by greater improvements in domains of physical and psychological health (under review), and existing research suggesting that RC growth in females is predicted by self‐reported increased focus on their overall health and community involvement, while males is predicted by a greater participation in meaningful activities, such as employment or education 30 . Ultimately it is unknown if investing in these interventions prospectively would be an effective tool and requires further study.…”
Section: Discussionmentioning
confidence: 74%
“…Previous correlates of higher RC have been lower‐risk substance use (as compared to higher‐risk substance use), 15 stable housing, 18 and employment 18 . Predictors of RC growth have also differed by sex, with work from our group showing that males exhibit differential growth driven by greater improvements in domains of physical and psychological health (under review), and existing research suggesting that RC growth in females is predicted by self‐reported increased focus on their overall health and community involvement, while males is predicted by a greater participation in meaningful activities, such as employment or education 30 . Ultimately it is unknown if investing in these interventions prospectively would be an effective tool and requires further study.…”
Section: Discussionmentioning
confidence: 74%
“…This article adds to a small but growing body of evidence regarding gender differences in recovery (Abreu Minero et al 2022;Collinson and Hall 2021;Best et al 2020), particularly highlighting variations in housing transitions of women during the recovery process (Martinelli et al 2020;Straaten et al 2016). The research question explored the application of a recovery capital framework to better understand their housing transitions.…”
Section: Discussionmentioning
confidence: 95%
“…Abreu Minero et al (2022) found that a significantly higher proportion of women in recovery than men report better management of general health, daily life tasks, and engagement in prosocial meaningful activities. However, women reported significantly higher rates of persistent barriers related to psychological health and domestic violence compared to men, whereas significantly higher rates of criminal justice barriers were found among men.…”
Section: Gendered Pathwaysmentioning
confidence: 99%
“…34 Existing research has also noted sex-based differences in RC growth, with predictors of growth in males being increased meaningful activities (like employment and education), whereas predictors in females were increased community involvement and improvements in overall health. 35 It remains speculative whether investing in RC prospectively would be an effective long-term intervention and requires additional study.…”
Section: Discussionmentioning
confidence: 99%
“…Investments in human capital through stable housing, such as Housing First Interventions, have shown significant decreases in emergency department visits and frequency of hospitalization; however, there were no differences in substance use 34 . Existing research has also noted sex-based differences in RC growth, with predictors of growth in males being increased meaningful activities (like employment and education), whereas predictors in females were increased community involvement and improvements in overall health 35 . It remains speculative whether investing in RC prospectively would be an effective long-term intervention and requires additional study.…”
Section: Discussionmentioning
confidence: 99%